2005
DOI: 10.1007/s10549-004-2227-6
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavone supplementation elevates erythrocyte superoxide dismutase, but not plasma ceruloplasmin in postmenopausal breast cancer survivors

Abstract: Soy isoflavone antioxidant effects may help prevent breast cancer re-occurrence, but isoflavone estrogen-like actions may increase breast cancer risk. These isoflavone actions can be reflected by effects on two copper enzymes activities, superoxide dismutase 1 (SOD 1), which has antioxidant function relevant to breast cancer prevention, and ceruloplasmin, which has its synthesis up-regulated by estrogen, and for which high values are associated with high breast cancer risk. A soy isoflavone-rich concentrate su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 48 publications
0
14
0
2
Order By: Relevance
“…The latter lack of effect occurred even if isoflavones were added well in excess of what oral intake could produce in serum samples. Similarly, a 4-week intake of an isoflavone concentrate can raise erythrocyte contents of the antioxidant enzyme superoxide dismutase 1, but this effect would not be expected to occur immediately after a single intake of isoflavones [10]. …”
Section: Introductionmentioning
confidence: 99%
“…The latter lack of effect occurred even if isoflavones were added well in excess of what oral intake could produce in serum samples. Similarly, a 4-week intake of an isoflavone concentrate can raise erythrocyte contents of the antioxidant enzyme superoxide dismutase 1, but this effect would not be expected to occur immediately after a single intake of isoflavones [10]. …”
Section: Introductionmentioning
confidence: 99%
“…SI have been shown to exhibit antioxidant effects both in vitro and in vivo . Disilvestro et al. (2005) reported that SI given in capsules elevate erythrocyte superoxide dismutase in human.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarker of cancer such as metalloproteinases [109], vitamin D hydroxylase [110], interleukins [111], omega-3 fatty acids [112], induced neutropenia [113], DNA adducts [114], DNA methylases [115], polymorphism [116], superoxide dismutase [117] have been discovered as potent indicators of nutraceutical chemopreventive mechanism. Still the action of phytochemicals and role of bacteria is not understood [118,119].…”
Section: Mechanism Of Cancer Prevention By Nutraceuticalsmentioning
confidence: 99%